Pycard and BC017158 Candidate Genes of Irm1 Locus Modulate Inflammasome Activation for IL-1β Production - Borrego, Andrea; Colombo, Francesca; de Souza, Jean Gabriel; Jensen, José Ricardo; Dassano, Alice; Piazza, Rocco; Rodrigues dos Santos, Barbara Anaís; Ribeiro, Orlando Garcia; De Franco, Marcelo; Cabrera, Wafa Hanna Koury; Icimoto, Marcelo Yudi; Starobinas, Nancy; et al. (Frontiers in Immunology, 2022)
We identified Pycard and BC017158 genes as putative effectors of the Quantitative Trait locus (QTL) that we mapped at distal chromosome 7 named Irm1 for Inflammatory response modulator 1, controlling acute inflammatory response (AIR) and the production of IL-1β, dependent on the activation of the NLRP3 inflammasome. We obtained the mapping through genome-wide linkage analysis of Single Nucleotide Polymorphisms (SNPs) in a cross between High (AIRmax) and Low (AIRmin) responder mouse lines that we produced by several generations of bidirectional selection for Acute Inflammatory Response. A highly significant linkage signal (LOD score peak of 72) for ex vivo IL-1β production limited a 4 Mbp interval to chromosome 7. Sequencing of the locus region revealed 14 SNPs between “High” and “Low” responders that narrowed the locus to a 420 Kb interval. Variants were detected in non-coding regions of Itgam, Rgs10 and BC017158 genes and at the first exon of Pycard gene, resulting in an E19K substitution in the protein ASC (apoptosis associated speck-like protein containing a CARD) an adaptor molecule in the inflammasome complex. Silencing of BC017158 inhibited IL1-β production by stimulated macrophages and the E19K ASC mutation carried by AIRmin mice impaired the ex vivo IL-1β response and the formation of ASC specks in stimulated cells. IL-1β and ASC specks play major roles in inflammatory reactions and in inflammation-related diseases. Our results delineate a novel genetic factor and a molecular mechanism affecting the acute inflammatory response.